The Concept of Madurese Customary Inheritance from the Perspective of Anthropology and Islamic Law - Masduki Masduki; Dzulfikar Rodafi; Syamsu Madyan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
The Pakaan Dajah Village community in Madura has a tradition of inheritance distribution that deviates from the faraid system of Islamic law. In other words, this village has an inheritance distribution system that does not conform to the distribution of inheritance as outlined in Islamic law. This study examines the implementation of customary inheritance from the perspective of legal anthropology and Islamic law using a juridical-empirical and juridical-sociological approach through qualitative methods. Data were collected through literature studies, interviews, observations, and documentation. The results show that inheritance distribution is carried out in two ways: during the testator's lifetime through a gift or will, and after the testator's death through deliberation and consensus among the heirs. This tradition tends to divide assets equally without distinction of gender, because men and women are considered to have equal value and roles in the family. This tradition is considered fairer and minimizes conflict, and is deeply rooted in society. Contextually, this inheritance practice can be justified because it is in line with the principle of deliberation and consensus in Islam and can be categorized as takharuj in Hanafi jurisprudence, although under certain conditions, the distribution can still be returned to the faroid system.